Search for Reserves in the Grip of the “Imputed”: Paradoxes of Our Education Strategy - Kh. G. Tkhagapsoev; M. M. Yakhutlov (Высшее образование в России)
The dominant orientation of the domestic strategy of higher education (standards, competencies) towards the current demands of the labor market slows down and constrains the development processes at universities. The ability and readiness to respond to the challenges of the future is steadily becoming a real basis for the success of higher education institutions in conditions of modern technological and socio-economic changes. Time and situation require taking into account in university strategies not only the demands of the labor market, but also the features of the future and trends in knowledge development. And this, in turn, dictates the need to liberalize the existing education strategy, as well as to “synchronize” the development of the university both with trends and prospects for the development of technologies and infrastructures, and the historical and epistemological patterns of knowledge development, its functions, ways of organization and forms of life.